Structural Transformation, Marketization, and Household Production around the World - Benjamin Bridgman; Georg Duernecker; Berthold Herrendorf (Center for Economic Studies and ifo Institute (CESifo), 2015)
We provide evidence on household and market production in 36 countries since 1960. On average the household sector accounts for almost half of total hours worked. As GDP per capita increases, the employment share of household production in total hours worked initially declines and then hardly changes while the employment shares of market goods and services decrease and increase. Estimating the value added of household production yields similar patterns. Labor productivity of household production is lower than and positively correlated with that in the market. These findings can be used as an input into quantitative work involving household production.
Keywords: O30; 330; household production; marketization; structural transformation